Spatial variability of soil properties of Mirzapur district of Uttar Pradesh - SEEMA, SEEMA; GHOSH, A K; ARADHANATHAKUR, ARADHANATHAKUR; YADAV, SUNITA (The Indian Journal of Agricultural Sciences, 2020)
To assess the chemical characterization of soils of Mirzapur District of Uttar Pradesh, the present investigation was undertaken using GPS and GIS techniques. In this study, 625 georeferenced soil samples were collected from different block of Mirzapur following random sampling approach in month of September-Decmber 2018. The soil samples were analyzed for different chemical parameters and the data along with GPS reading were used for the preparation of soil thematic maps using interpolation method and the interpolated maps were analysed with geostatistical parameters and the corresponding kriging maps for pH, electrical conductivity (EC), soil organic carbon (SOC), and available nitrogen, phosphorus, potassium and cationic micronutrients (Zn, Fe, Cu, Mn of cations) were prepared. The soil thematic maps clearly shown that a major area of the Mirzapur was alkaline, non-saline, low in OC, medium in available Potassium. The mean content of soil pH, EC, Organic Carbon, available Nitrogen, phosphorus and Potassium in surface soils were 7.5, 0.09 dS/m, 5.4 g/kg, 128.08, 37.01 and 338.65 kg/ha respectively.